2012
DOI: 10.1590/s0100-204x2012000600020
|View full text |Cite
|
Sign up to set email alerts
|

Defesas induzidas por herbivoria e interações específicas no sistema tritrófico soja-percevejos-parasitoides de ovos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a influência de voláteis de soja, induzidos pela herbivoria dos percevejos Euschistus heros e Nezara viridula, no comportamento de busca de hospedeiros dos parasitoides Telenomus podisi e Trissolcus basalis. Plantas injuriadas pela alimentação dos percevejos foram utilizadas como estímulos em bioensaios com fêmeas dos parasitoides, em olfatômetro de dupla escolha tipo Y. Telenomus podisi respondeu somente a voláteis liberados pela soja após a herbivoria de E. heros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition, the tritrophic relation of plant/pest/parasitoid must be considered. Other studies have shown that the egg parasitoid T. podisi prefers plants damaged by E. heros to healthy plants (Lopes et al 2012) which emphasizes the need for further experiments with Bt-plants under field conditions in order to clarify this relationship. However, since no adverse impact of Bt soybean above T. podisi sex ratio was observed in our study, these results suggest that E. heros egg is nutritionally and chemically similar to the eggs originated from stink bugs which fed on both Bt and non-Bt soybean pods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tritrophic relation of plant/pest/parasitoid must be considered. Other studies have shown that the egg parasitoid T. podisi prefers plants damaged by E. heros to healthy plants (Lopes et al 2012) which emphasizes the need for further experiments with Bt-plants under field conditions in order to clarify this relationship. However, since no adverse impact of Bt soybean above T. podisi sex ratio was observed in our study, these results suggest that E. heros egg is nutritionally and chemically similar to the eggs originated from stink bugs which fed on both Bt and non-Bt soybean pods.…”
Section: Discussionmentioning
confidence: 99%
“…podisi to discriminate between footprints of different stink bug species. Selective responses of these parasitoids are also reported for stimuli used in the early stages of a host search, such as plant volatiles (Lopes et al ., ) and host semiochemicals (Laumann et al ., ; Tognon et al ., ). Similarly, selective responses are reported for stimuli used after habitat location, such as host vibratory signals (Laumann et al ., , ) colour of the substrate (Aquino et al ., ) and egg volatiles (Michereff et al ., ; Tognon et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their specificities, regarding the preferred host, both are found parasitizing eggs of the main soybean stink bug pests (Lopes et al 2012). Parasitism rates reach 80 % for T. podisi (Pacheco & Corrêa-Ferreira 2000) and 60 % for T. basalis (Corrêa-Ferreira & Moscardi 1995).…”
Section: Abstract Resumomentioning
confidence: 99%